Pembuatan Lorong Bahasa Sebagai Salah Satu Inovasi Media Pembelajaran di SMP Negeri 2 Bukit Batu - Nasrizal Nasrizal; Asya Thalia Salsabila; Dini Aulia Putri; Dwi Mulyaningsih; Zahratul Aini Bediona; Ikhtiara Amwan Nisa Br Siregar; Trisan Ayu Ildayani; Syarifah Fathul Arini; Willy Akbar Gahani; Smile Peniel Marplus T; Gilang Frisqi Putra Hanafi (Universitas 45 Surabaya, 2025)
The rapid development of technology has had a big influence on education, especially in learning media. For this reason, regular learning innovations are needed. The aim of this service activity is to raise awareness among school residents about the importance of innovation both in terms of learning methods and learning media. Alley Language is one of the efforts made to create an innovative learning media. The method used in this service activity begins with conducting a survey at the target location. This was followed by discussion activities with the aim of discussing preparations and requirements for running this program. Then the next step is to provide counseling or introduction to a foreign language, namely Japanese, to all students of SMP Negeri 2 Bukit Batu. Then the final step is implementing the Language Hallway program which starts from preparing to make a board that will be installed in the Language Hallway to installing the Language Hallway. The result of this service program is a new facility at SMP Negeri 2 Bukit Batu, namely a foreign language learning medium located in one of the corridors of SMP Negeri 2 Bukit Batu.